2000
DOI: 10.1055/s-0037-1614133
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Biological Activity of the Active Metabolite of Clopidogrel

Abstract: SummaryLike ticlopidine, the ADP receptor antagonist clopidogrel is inactive in vitro and must be administered i.v. or orally to exhibit antiaggregatory and antithrombotic activities. We have previously shown that hepatic metabolism is necessary for activity. This study demonstrates that an active metabolite can be generated from human liver microsomes incubated with clopidogrel. Using several analytical methodologies (LC/MS, NMR, chiral supercritical fluid chromatography), we have identified its structure. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
473
0
10

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 692 publications
(496 citation statements)
references
References 22 publications
10
473
0
10
Order By: Relevance
“…The thienopyridine compounds are prodrugs which have to be metabolized by the liver in order to generate active metabolites. The active metabolite of clopidogrel [107] covalently binds cysteine residues of the P2Y 12 receptor, thus precluding the binding of ADP [108][109][110]. Moreover, it has been recently reported that clopidogrel's active metabolite disrupts homopolymers of the P2Y 12 receptor expressed in lipid rafts and partitions them out of lipid rafts [111], pointing to the importance of oligomerization and membrane localization on the function of this receptor.…”
Section: The Platelet P2 Receptors As Molecular Targets For Antithrommentioning
confidence: 99%
“…The thienopyridine compounds are prodrugs which have to be metabolized by the liver in order to generate active metabolites. The active metabolite of clopidogrel [107] covalently binds cysteine residues of the P2Y 12 receptor, thus precluding the binding of ADP [108][109][110]. Moreover, it has been recently reported that clopidogrel's active metabolite disrupts homopolymers of the P2Y 12 receptor expressed in lipid rafts and partitions them out of lipid rafts [111], pointing to the importance of oligomerization and membrane localization on the function of this receptor.…”
Section: The Platelet P2 Receptors As Molecular Targets For Antithrommentioning
confidence: 99%
“…Concern about the toxic effects of ticlopidine (neutropenia, thrombotic thrombocytopenic purpura) led to the development of a similar prodrug, clopidogrel, that did not have these adverse effects and has become widely used. Both ticlopidine and clopidogrel exert their inhibitory effect through an active metabolite that has a thiol group that reacts irreversibly with a cysteine residue of P2Y 12 [138].…”
Section: Drugs That Act On the P2y 12 Receptormentioning
confidence: 99%
“…1 Recently, it was shown that cytochrome P-450, isoform 3A4 (CYP3A4), is primarily responsible for the metabolism and activation of clopidogrel in vivo. 2 Several studies have shown that clopidogrel decreases the incidence of coronary artery stent thrombosis and is approved for reduction of myocardial infarction, stroke, and vascular death in patients with atherosclerotic vascular disease.…”
mentioning
confidence: 99%